A note on performance indicators for agricultural economic journals. (20th December 2021) - Finger, Robert; Droste, Nils; Bartkowski, Bartosz; Ang, Frederic
Abstract: We investigate various performance indicators of ten leading journals in the field of Agricultural Economics and Policy over the period from 2000 to 2020. More specifically, we combine various data sources to derive a coherent record of indicators including acceptance rates, times between submission and first response and impact factors. We show that, for the discipline at large, the turn‐around times have decreased, and impact factors have increased substantially over time. However, this has been accompanied by a sharp decrease in the proportion of accepted articles. Our analysis also reveals large differences across journals in all dimensions. Results show there is no free lunch, that is, authors face trade‐offs. For example, submitting to a higher impact factor journal means on average longer turn‐around time and lower acceptance rates. The dataset compiled and presented here gives the first coherent overview of relevant information to guide authors' submission decisions, and inform our fellow professionals.